(untitled) (Anclajes, 2013)
The New Man ideal depicted on Ernesto “Che” Guevara’s Episodes of the Cuban Revolutionary War, and invoked as a social model in the discourse of the new revolutionary Cuban state after 1959 is taken here as a reference for reading Reinaldo Arena’s short story “The parade begins”. Contrary to Guevara’s text, Arenas proposes that the revolutionary event does not mean the final de-alienation and emancipation of the repressed original subject, but the chance of opening up a space that allows to escape from the socially prescribed identities (man, warrior, hero) and explore new possible forms of subjectivity.